Planning project stakeholder engagement from a sustainable development perspective - Gilbert Silvius; Ron Schipper (Administrative Sciences, 2019)
Sustainability is one of the most important challenges of our time. As the role that projects play in sustainable development is still developing, the integration of the concepts of sustainability into project management is an important trend in project management today. However, despite the conceptual understanding of this integration, the literature still provides little practical guidance on how to apply sustainability to project management. This article aims to contribute to the integration of sustainable development and project stakeholder management by developing practical tools and frameworks that enable project managers to identify stakeholders, assess stakeholders, and plan stakeholder engagement activities with a consideration of sustainable development. The study takes a pragmatic design science approach in developing these tools and frameworks. The resulting frameworks build upon the concepts of sustainable development and form an elaboration of the documented practices of project stakeholder management.
Keywords: 350; sustainable project management; stakeholders; project stakeholder management